International Drug Safety Monitoring - A. S. Kazakov; E. V. Shubnikova; M. A. Darmostukova; I. I. Snegireva; G. V. Kutekhova; K. E. Zatolochina; N. Yu. Velts; D. A. Kaperko; Yu. V. Olefir (Безопасность и риск фармакотерапии)
In the 1960s, following the Thalidomide Disaster, the World Health Organization (WHO) initiated the development of an international drug safety monitoring programme. The objectives of this WHO programme are to improve the quality and safety of pharmaceuticals, and to support public health programmes by providing information for effective assessment of the risk-benefit ratio of medicinal products. The paper outlines the main focus areas of the programme and the mechanism of interaction between the countries involved. It summarises the functions of the WHO Collaborating Centre for International Drug Monitoring located in Uppsala, namely, accumulation and assessment of data on efficacy, inefficacy and risks of medicinal products, which are communicated by the participating countries, and provision of reliable and coherent data to specialists. The paper provides a review of online resources and methods used by VigiBase — global database of adverse drug reactions — that make it possible to search and analyse the data statistically. It describes the functions of the national monitoring centres located in different regions, and their interaction with the WHO. The dissemination of objective and reliable medical information throughout the world, promotion of pharmacovigilance as a science, creation of international partnerships and pooling of expertise from different countries allow for a significant improvement in the safety of pharmacotherapy.